2014
DOI: 10.1099/ijs.0.065375-0
|View full text |Cite
|
Sign up to set email alerts
|

Aquibacillus halophilus gen. nov., sp. nov., a moderately halophilic bacterium from a hypersaline lake, and reclassification of Virgibacillus koreensis as Aquibacillus koreensis comb. nov. and Virgibacillus albus as Aquibacillus albus comb. nov.

Abstract: Aquibacillus halophilus gen. nov., sp. nov., a moderately halophilic bacterium from a hypersaline lake, and reclassification of Virgibacillus koreensis as Aquibacillus koreensis comb. nov. and Virgibacillus albus as Aquibacillus albus comb. nov. A novel Gram-stain-positive, moderately halophilic bacterium, designated strain B6B T , was isolated from the water of an Iranian hypersaline lake, Aran-Bidgol, and characterized taxonomically using a polyphasic approach. Cells of strain B6B T were rod-shaped, motile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…The isoprenoid quinones in freeze-dried cells were analysed by HPLC [48]. Chemotaxonomic data indicated that strain TKL69 T utilized MK-7 as the major respiratory quinone, which was consistent with S. xinjiangensis CGMCC 1.12331 T , A. halophilus KCTC 13828 T and O. contaminans DSM 22953 T [12,45,49]. The cell-wall amino acids and characteristic sugar in the whole-cell hydrolysates were detected by TLC [50].…”
Section: Physiology and Chemotaxonomymentioning
confidence: 77%
See 2 more Smart Citations
“…The isoprenoid quinones in freeze-dried cells were analysed by HPLC [48]. Chemotaxonomic data indicated that strain TKL69 T utilized MK-7 as the major respiratory quinone, which was consistent with S. xinjiangensis CGMCC 1.12331 T , A. halophilus KCTC 13828 T and O. contaminans DSM 22953 T [12,45,49]. The cell-wall amino acids and characteristic sugar in the whole-cell hydrolysates were detected by TLC [50].…”
Section: Physiology and Chemotaxonomymentioning
confidence: 77%
“…Although most of those genera are aerobic [3][4][5][6][7], some are found to be either facultatively anaerobic [8] or strictly anaerobic [9]. While most genera share the common feature of being Gram-stain-positive [10][11][12], some are found to be Gram-stain-variable [13]. Members of the Bacillaceae have been isolated from various habitats, showing strong environmental adaptability with some members being identified as halophilic [14,15], thermotolerant [16] and alkaliphilic bacilli [17,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such microorganisms are commonly found in evaporation ponds, sea waters, saline salterns, and sediments, as well as other saline habitats (Maheshwari and Saraf, 2015; Lee et al, 2018). In particular, bacteria belonging to the Bacillales order are found in almost every environment on Earth from the stratosphere (Sass et al, 2008), through to NaCl-hypersaline environments, such as salterns (Garabito et al, 1998), saline soils (Zahran, 1997), freshwater lakes (Bagheri et al, 2012; Amoozegar et al, 2014, 2016), and even in alkaline lakes (Weisser and Trüper, 1985). Moreover, they have been isolated from brines with different chemical composition including MgCl 2 (Hallsworth et al, 2007; Sass et al, 2008), Na 2 CO 3 (Jones et al, 1998), and NaCl/LiCl (Rodríguez-Contreras et al, 2013; Martínez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These members have mostly been isolated from environments such as salt lakes, salterns, seawater, saline soils, soda lakes and salted foods (Arahal & Ventosa, 2002;de la Haba et al, 2011;Wang et al, 2011). Some recently described genera from the family include Aquibacillus (Amoozegar et al, 2014), Sinibacillus (Yang & Zhou, 2014), Saliterribacillus (Amoozegar et al, 2013) and Domibacillus (Seiler et al, 2013). In this study we propose a novel species of a new genus in the family Bacillaceae, based on characterizing a strain (designated S5 T ) using the minimal standards proposed for the description of new taxa of aerobic endospore-formers (Logan et al, 2009).…”
mentioning
confidence: 99%